Recognition of Gonadal Development in Eriocheir sinensis Based on the Impulse of Love at First Sight - Jiang, Jingjing; Su, Shengyan; Lai, Ting; Feng, Wenrong; Li, Feifan; Tian, Can; Gao, Yang; Munganga, Brian Peelekelo; Tang, Yongkai; Xu, Pao (Frontiers in Physiology, 2022)
Given the difficulty in identifying individuals with different degrees of ovarian development, we developed a new device utilizing the hypothesis of mutual attraction behavior between male and female crabs with mature gonads by releasing the sexual pheromone so they could be examined. From a total of 40 female crabs, 10 were isolated within half an hour. Histological analysis showed that the ovaries of crabs in the isolated group were in stage IV, while those of the control groups were in stage III. In addition, progesterone (PROG) in experimental groups was significantly reduced compared with the control group (p < 0.05), but no significant difference was detected in estradiol (E2). In response to the different developmental stages, hemolymph biochemical indices and the determination of gonadal fatty acids profiles were explored. The results indicated only C18:4 showed a significant difference between these two groups. A transcriptome was generated to determine the genes involved in the mutual attraction process; differentially expressed genes (DEGs) were significantly related to gonadal development. Therefore, the device can be used to isolate Chinese mitten crabs with stage IV ovarian development.